PELAKSANAAN INTERNSHIP TRAININGDALAM MENINGKATKAN SDM YANG BERKUALITASDI NIRWANA GARDENS RESORT BINTAN - Yoga Saputra, - (2009)
Yoga Saputra, "Internship Training Implementation for Increasing Qualified Human Resources in Nirwana Gardens Resort Bintan", with Prof. Dr. Darsihardjo, Ms. And Drs. Amir Husaini as the assist lecturers. Internship Training is one of the necessary requirements and become an obligation before finishing the study in university. Since this is an opportunity to apply the knowledge in real activity form. Therefore some factors that are needed to determine the available internship training activities are: skill, knowledge, standard & procedure, job priorities & job description and also feedback. As a result from this internship training activity is to produce high quality human resources. In this research, the object is trainees in Nirwana Gardens Resort Bintan. Whereas the variable X is the realization of internship training, and the variable Y is the improvement of qualified human resources. This research uses descriptive quantitative method, which uses questioners with census sample, then as the result are 60 respondents as the samples. The data analysis technique that used in this research is correlation analysis technique and simple linier regression technique with using determination coefficient. This research result presents that the implementation of internship training influences 15.8 % of the increasing of qualified human resources, and 84.2% is influenced by others factors. This point shows that the implementation of internship training is not the only one way to increase the qualified human resources. Therefore, the suggestions to the management of Nirwana Gardens Resort Bintan so the elements could give benefit in the development of human resources quality. So in the implementation of internship training, management could give the opportunities to the trainees to have some creativity with their jobs, which enable them to produce new innovation. This case is pointed to increase the human resources with high quality which direct to the company profit.